Modifikasi Lagu Sholawat untuk Pembelajaran Bahasa Inggris di Pesantren - Maisarah Maisarah (IAI Darussalam, 2018)
English is one of the foreign languages ​​that must be taught in Indonesia including in the pesantren environment. But teaching English in pesantren is often less fun (using only classical methods or lectures only). As a result, their mastery of English is also not good. The vocabulary of the santri tends to be very limited. Therefore, this research aims to create English songs with